Pengaruh Metode SAS (Struktural Analitik Sintetik) Terhadap Keterampilan Menulis Siswa Kelas II Pada Pembelajaran Bahasa Indonesia Di Mis An-Nazmaiyah - Wanda Amelia Purba; Sahkholid Nasution (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the effect of the Structural Analytical Synthetic (SAS) method on the writing skills of second-grade students in Indonesian language learning at MIS An-Nazmaiyah. Writing is one of the important and fundamental language skills, but in reality many second-grade students still show low writing skills, especially in forming simple sentences with correct spelling. This study aims to determine whether the application of the SAS method has a significant effect on students' initial writing skills. This study uses a quantitative approach with a One Group Pretest–Posttest design, involving 25 second-grade students selected using a saturated sampling technique. Data were obtained through a writing assessment rubric that includes aspects of letter clarity, spelling accuracy, coherence between sentences, suitability to the object discussed, appropriate word use, and neatness of writing. Data analysis was carried out using descriptive and inferential statistics, namely by conducting the Shapiro-Wilk normality test, followed by a Paired Sample T-Test. The results showed that the average student score increased from 53.18 in the pretest to 74.52 in the posttest. The results of the Paired Sample T-Test produced a t-value of 8.291 with a significance value of 0.000 <0.05, so H₀ was rejected. From the results of the study, it can be concluded that the SAS method has a significant influence on the writing skills of class II students of MIS An-Nazmaiyah and is proven to be effective as an alternative method for learning Indonesian at the elementary madrasah level.